Effects of transformational coaches on athlete mental toughness: Dual mediating roles of task-involving climate perception and coach-athlete relationship - Kao, S.-F.; Tsai, C.-Y.; Wang, S.-B.; Hsieh, M.-H.; Hsu, C.-M. (International Journal of Sports Science & Coaching, 2025)
Research on coach transformational leadership and athlete mental toughness has yet to fully explore the influence of processes and mechanisms linking the two. This study examines two mediating pathways: task-involving climate perception and coach-athlete relationship quality. Grounded in self-determination and conservation of resource theories, we propose that coach transformational leadership fosters a supportive environment and offers a leader-follower exchange relationship as resources, which in turn strengthens mental toughness. We surveyed 301 volleyball players and utilized path analyses with bootstrapping methods to examine our hypotheses. Our findings indicate that an athlete's task-involving climate perception and coach-athlete exchange relationship play pivotal roles in determining the indirect impacts of coach transformational leadership on athlete mental toughness. We identify the intricate nature of coach transformational leadership, which encourages the development of athlete self-determination and cultivates high-quality coach-athlete relationships, consequently bolstering athlete mental toughness.